Martes americana - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Martes americana (Turton, 1806). In Linnaeus, Gen. Syst. Nat., 1:60. TYPE LOCALITY: "North America". DISTRIBUTION: Alaska and Canada south to N California, south in the Sierra Nevada and Rocky Mtns to 35°N. SYNONYMS: abieticola Preble, 1902; abietinoides Gray, 1865; actuosa Osgood, 1900; atrata Bangs, 1897; boria Elliot, 1905; brumalis Bangs, 1898; caurina Merriam, 1890; humboldtensis Grinnell and Dixon, 1926; huro F. Cuvier, 1823; kenaiensis Elliot, 1903; leucopus Kuhl, 1820; martinus Ames, 1874; nesophila Osgood, 1901; origenes Rhoads, 1902; sierrae Grinnell and Storer, 1916; vancouverensis Grinnell and Dixon, 1926; vulpina Rafinesque, 1819. COMMENTS: May be conspecific with martes, melampus, and zibellina (Anderson, 1970; Hagmeier, 1961). See Clark et al. (1987, Mammalian Species, 289). Published as part of W. Christopher Wozencraft, 1993, Order Carnivora, pp. 279-348 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 319, DOI: 10.5281/zenodo.7359191